The effect of nutrition counseling on nutritional status for breast cancer patients in dr. Sardjito Hospital, Indonesia - Susetyowati Susetyowati; Sri Retna Dwidanarti; Retno Pangastuti; Hanifah Wulandari; Farah Faza; Nadira D'mas Getare Sanubari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Nutrition counseling in breast cancer (BC) patients show long-term adherence to a dietary pattern and effects on nutritional status and quality of life (QOL).Objective : We evaluated the effects of nutrition counseling for nutrients intake dan nutritional status improvement among breast cancer patients.Material and Methods: This research was conducted in a Pre-experimental design; one group pretest-postest design was conducted on 45 BC patients who underwent radiotherapy for five weeks in the Radiotherapy Unit, dr. Sardjito Hospital, Indonesia. Nutrition counseling was demonstrated by trained fieldworkers to 45 participants using a nutrition booklet for BC patients and a food model as an intervention technique. Continuous nutrition counseling was given three times: weeks 1, 3, and 5 of radiotherapy. We examined anthropometry, biochemical, physical, dietary, and Patient-Generated Subjective Global Assessment (PG-SGA) questionnaire to obtain nutritional status.Results: Most of the participants had a body mass index (BMI) ≥25 kg/m2 (62.2%). After the participants were receiving nutrition counseling, there were increases in intake of energy, protein, carbohydrate, vitamin A, vitamin C, and vitamin E amounted 124.54 kcal, 8.12 g (p=0.01), 5.84 g, 234.43 mg, 0.042 mg, and 0.44 mg, respectively. Intake of fruits and vegetables improved on the first, third, and fifth week (1.44, 2.36, and 4.03 portion/day, respectively) (p=0.001). Handgrip strength (HGS) showed slight improvement (p=0.081). However, HGS ameliorated from 15.85 kgs in the early to 16.97 kgs in the end stage of therapy. Bodyweight decreased 0.28 kg; however, there are no changes in PG-SGA score, hemoglobin (Hb), and albumin levels.Conclusion: Nutrition counseling improves patients’ nutrition intake despite there is no significant alteration in nutritional status. In addition, nutrition counseling for breast cancer patients during radiotherapy is essential to maintain and improve nutrient intake and nutritional status. In the long-term period, it might be affected to improve quality of life.